Metode Pendidikan Dalam Al-Qur'an (Kajian Tafsir Tematik) - Mochamad Syaifulloh (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2017)
As a component of science, the method can deliver an educational process can achieve theireducation goal quickly and precisely. This will happen when the methods of education andteaching which is in line with the substance and purpose. Therefore an educator must mastermany learning methods, so that he can choose the method that is appropriate to thecircumstances. In the world of Islamic education, learning and educational goals let inaccordance with the Koran and the Hadith as the source of the basic teachings of Islam. In thetwo sources of the law there had to be a strong foundation on educational methods, as hasbeen done by the Prophet Muhammad in preaching and educating Muslims. Through thestudy of thematic interpretation (Tafsir thematic), this study aims to uncover methods ofeducation contained in the Koran, as well as explore the hadiths relevant to such methods.The results of this study indicate that there are several methods of education in the Quraninclude: storytelling (Hud : 120), and answer method (Al-Baqarah : 189), the method ofwisdom, advice, discussion (An- Nahl : 125), and the method of demonstration (al-Kahf : 77).Keywords: Methods, Education, Tafsir thematic. thematic interpretation.